Extracorporeal membrane oxygenation in the pediatric population – who should go on, and who should not. Issue 3 (June 2020) - Etchill, Eric W.; Dante, Siddhartha A.; Garcia, Alejandro V.
Abstract : Purpose of review: The role of extracorporeal membrane oxygenation (ECMO), a method of providing cardiorespiratory support in instances of cardiac or respiratory failure, in neonates and children continues to expand and evolve. This review details the current landscape of ECMO as it applies to neonates and children. Recent findings: Specifically, this review provides the most recent evidence for which patients should be considered for the various forms of ECMO including venovenous ECMO, venoarterial-ECMO, and extracorporeal cardiopulmonary resuscitation. Specific topics to be discussed include indications and contraindications for the different types of ECMO in neonates and children, anticoagulation strategies and ways to monitor end-organ function, outcomes specific to the different types and populations with a focus on meaningful survival to discharge and neurologic outcomes, and consideration of special populations such as low birth weight infants, traumatically injured patients, and children who received recent bone marrow transplants. This review also discusses still unanswered questions surrounding the most appropriate use of ECMO as its role and applications continue to evolve. Summary: With rapidly increasing utilization of ECMO, neonatologists and pediatricians should be aware of the most recent evidence guiding its indications, applications, and limitations.